On Semigroup Ideals and Generalized n-derivations in Near-rings - Ashraf, Mohammad; Siddeeque, Mohammad Aslam (Sarajevo Journal of Mathematics, 2024)
In the present paper, we investigate the commutativity of addition and ring behavior of 3-prime near-rings satisfying certain conditions involving generalized n-derivations on semigroup ideals. Moreover, examples justifying the necessity of the 3-primeness condition in all the results are provided.